Production of Radish Plants (Raphanus sativus) Due to Giving Bokashi and SP-36 - Uly J. Riwu Kaho; Joritha Naisanu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Radish plants as a food ingredient, almost all parts of the plant can be eaten raw as fresh vegetables or cooked as vegetables. The community's need for radish continues to increase as indicated by an increase in the amount of production. In 2018 radish production was recorded at 32,381 tons, in 2019 production decreased to 27,279 tons, while in 2020 production increased again to 39,048 tons. The solution in increasing radish production is by fertilizing using organic and inorganic fertilizers. The aim is to determine the interaction between SP-36 and bokasih on radish crop yields. The plan utilized was a randomized block plan (RBD) in a factorial example with two variables. The outcomes acquired: The treatment of bokashi and SP36 composts meaningfully affected plant level, number of leaves, tuber length, tuber distance across and tuber weight of radish plants. The connection between the utilization of Bokashi and SP36 composts gave the best outcomes on the normal plant level, number of leaves, tuber measurement and tuber weight of radish plants.